Unraveling Aβ-Mediated Multi-Pathway Calcium Dynamics in Astrocytes: Implications for Alzheimer’s Disease Treatment From Simulations - Liu, Langzhou; Gao, Huayi; Zaikin, Alexey; Chen, Shangbin (Frontiers in Physiology, 2021)
The accumulation of amyloid β peptide (Aβ) in the brain is hypothesized to be the major factor driving Alzheimer’s disease (AD) pathogenesis. Mounting evidence suggests that astrocytes are the primary target of Aβ neurotoxicity. Aβ is known to interfere with multiple calcium fluxes, thus disrupting the calcium homeostasis regulation of astrocytes, which are likely to produce calcium oscillations. Ca2+ dyshomeostasis has been observed to precede the appearance of clinical symptoms of AD; however, it is experimentally very difficult to investigate the interactions of many mechanisms. Given that Ca2+ disruption is ubiquitously involved in AD progression, it is likely that focusing on Ca2+ dysregulation may serve as a potential therapeutic approach to preventing or treating AD, while current hypotheses concerning AD have so far failed to yield curable therapies. For this purpose, we derive and investigate a concise mathematical model for Aβ-mediated multi-pathway astrocytic intracellular Ca2+ dynamics. This model accounts for how Aβ affects various fluxes contributions through voltage-gated calcium channels, Aβ-formed channels and ryanodine receptors. Bifurcation analysis of Aβ level, which reflected the corresponding progression of the disease, revealed that Aβ significantly induced the increasing [Ca2+]i and frequency of calcium oscillations. The influence of inositol 1,4,5-trisphosphate production (IP3) is also investigated in the presence of Aβ as well as the impact of changes in resting membrane potential. In turn, the Ca2+ flux can be considerably changed by exerting specific interventions, such as ion channel blockers or receptor antagonists. By doing so, a “combination therapy” targeting multiple pathways simultaneously has finally been demonstrated to be more effective. This study helps to better understand the effect of Aβ, and our findings provide new insight into the treatment of AD.